The Complexity of Neuroenhancement and the Adoption of a Social Cognitive Perspective - Zelli, Arnaldo; Lucidi, Fabio; Mallia, Luca (Frontiers in Psychology, 2015)
This contribution attempts to provide a broad perspective to the psychological study of neuroenhancement. It departs from the assumption that, as the use of performance enhancing substances in sport, the use of substances with the aim of improving one’s cognitive, motivational and affective functioning in academic domains is a goal-directed behavior. As such, its scientific study may very well benefit from an analysis taking into account the psychological processes regulating people’s behavioral intentions and decisions. Within this broad framework, this contribution addresses several issues that currently seem to characterize the debate in the literature on neuroenhancement substances (NES) use. The first conceptual issue seeks to determine and define the “boundaries” of the phenomenon. The second issue concerns the empirical evidence on the prevalence of using certain substances for the purpose of neuroenhancement. Finally, there is a debate around the ethical and moral implications of neuroenhancement. Along these lines, the existing psychological research on neuroenahncement has adopted mainly sociological and economic decision-making perspectives, greatly contributing to the psychological discourse about the phenomenon of neuroenhancement. However, we argue that the existing psychological literature does not offer a common, explicit and integrated theoretical framework. Borrowing from the framework of doping research, we recommend the adoption of a social cognitive model for pursuing a systematic analysis of the psychological processes that dynamically regulate students’ use of NES over time.